Innovation in the arts : concepts, theories, and practices - White, Jason C., 1982- (Abingdon, Oxon : Routledge, 2023)
"This concise guide aims to increase what we understand by innovation in the arts and identify and support opportunities and strategies for the unique ways in which artists and arts administrators think about, engage in, and pursue successful innovation in their diverse creative practice. Innovations in the Arts are often marginalized from a research perspective, in part because of the lack of a sound and compelling theoretical framework to support and explain process distinctions from business and management innovation. This book identifies three key concepts - art innovation; art movement innovation and audience experience innovation - supported by formal theory for each concept presented and evidenced through case studies in art history. In this way, the book enables readers to identify, explain and support their innovation efforts as visual, literary and performing artists and arts administrators. It also explores strategies for pursuing innovation in practice. Drawing attention to the unique ways in which artists and arts administrators think about and engage in innovation, this readable book will be essential reading for students in all aspects of the creative and cultural industries and an essential guide to developing and promoting innovation in the arts for practitioners and researchers alike"--
Key terms for mutual understanding -- A theory of art innovation -- A theory of art movement innovation -- A theory of audience experience innovation -- Conclusions and suggested directions.
OCLC-licensed vendor bibliographic record.
Keywords: Creation (Literary, artistic, etc.); Artists -- Psychology; Arts administrators -- Psychology; Creative thinking; Organizational change; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities; BUSINESS & ECONOMICS / Entrepreneurship; ART / Business Aspects